Regulation of muscle atrophy and limb regeneration during molting in crustaceans: characterization of a muscle-specific calpain and a limb autonomy factor - Yu, Xiaoli, author; Mykles, Donald, advisor; Reddy, A. S. N., committee member; Voss, Randall, committee member; Wilson, Tomas, committee member (Colorado State University. Libraries, 2002)
Molting in crustaceans requires the precise coordination of virtually all-major organ systems. During molting, regeneration of lost appendages must be coordinated with various other physiological processes to ensure successful exuviation. If a limb regenerate (limb bud) is removed before a critical period during premolt, growth of any remaining primary (1°) limb buds (LBs) stops to allow regeneration of a secondary (2°) LBs. I show that 2° LBs contain a factor, termed limb autotomy factor-proecdysis (LAFpro), that blocks molting when injected into premolt animals. Secondary LB extracts inhibited the growth rate of 1° LBs about 68% during the first week of injection, while 1° LB extract had no effect. LAFpro was stable when boiled for 15 min in deionized water, but was inactivated when boiled in 0.1 M acetic acid and with the incubation of Proteinase K. Limb bud autotomy reduced the ecdysteroid levels in the hemolymph of premolt animals. These data suggest that LAFpro is a molt-inhibiting hormone-like polypeptide that suppresses ecdysteroid synthesis and secretion by the Y-organs.

Crustacean muscles contain four calcium-dependent cysteine proteinases (CDPs or calpains) which are involved in the degradation of myofibrillar proteins during molting. Using nested PCR and inverse PCR, a full-length (1977 bp) lobster calpain gene (Ha-CalpM) was cloned. The deduced amino acid sequence of the polypeptide (575 aa, 66.3 kDa) has high sequence identity to other calpains. Ha-CalpM contains three domains with domain IV absent. Gene expression analysis revealed that Ha-CalpM is highly expressed in skeletal muscle, with little or no expression in other tissues. Real-time PCR showed that it is up regulated during the premolt stage in claw muscles undergoing atrophy. A polyclonal antibody raised against a unique amino acid sequence in domain I was used to determine the relative amounts and the location of Ha-CalpM protein expressed in lobster tissues. It detected 62-kDa and 68-kDa proteins in western blots. Immunocytochmistry indicated that Ha-CalpM is localized in both the cytoplasm and nuclei of muscle fibers.
Keywords: cellular biology; molecular biology